Evaluation for Faithful Reproduction of Star Fields in a Planetarium - Tanaka, Midori; Horiuchi, Takahiko; Otani, Ken'ichi; Hung, Po-Chieh (Electronic Imaging, 2017)
In order to investigate factors necessary for reproducing actual star images in a planetarium, for this article, the authors conducted a psychophysical experiment using projection stimuli generated by changing three parameters of the stars: color, luminance, and size. A reference projection pattern was designed to be faithful to the actual starry sky perceptually (rather than physically) by an experienced group with abundant astronomical observation experience. A reproduction system was constructed to project ten types of star image patterns to a planetarium dome using different parameters. Then, evaluation experiments with twenty observers were conducted. The results of the experiment indicate that the intensity of the stars was sensitive to the fidelity of the reproduction, and in either case of change (whether the star was bright or dark compared to the reference pattern), the result was a loss of fidelity. In addition, although the fidelity was improved when the size of the projected star was small, for stars that were projected larger than the reference pattern, the result was remarkably negative. As for differences in color, the evaluation results suggested that the tolerance to loss of fidelity was wide. © 2017 Society for Imaging Science and Technology. [DOI: 10.2352/J.ImagingSci.Technol.2017.61.6.060401]